Assessment of Adverse Drug Reaction Due to Cancer Chemotherapy in a Teaching Oncology Hospital in Isfahan, Central of Iran - Vaseghi, Golnaz; Abed, Alireza; Jafari, Elham; Eslami, Neda; Eshraghi, Azadeh (Reviews on Recent Clinical Trials, 2016)
Introduction: Adverse Drug Reactions (ADRs) are common in hospitalized oncology patients. The kinds of ADRs experienced by cancer patients are varied. Therefore, the identification of appropriate manner in order to prevent ADRs may improve patient outcome. Aims: The present study evaluated the incidence, frequency and common types of adverse drug reactions among hospitalized oncology patients. Methods: Patients hospitalized at a university oncology center (children and adult) during the calendar year 2012 were randomly selected. Data were collected by reviewing of medical records. The outcome measures included the incidence of observed ADRs and ADR-related admissions and achieving strategies to prevent the emergence of chemotherapy side effects. Results: ADRs frequently occurred in the age group less than 20 years (22%). Prevalence of leukemia (27%), colon cancer (16.5%) and breast cancer (14%) was higher in our region. Most ADRs were recorded in patients receiving cisplatin (44%), doxorubicin (24%) and 5-fluouracil (20%) as chemotherapy. The most frequently observed ADRs were nauseavomiting, neutropenia and constipation in both pediatric and adult population. Conclusion: This study shows that ADRs occur more frequently in the pediatric group compared to adults. Therefore, optimum use of preventative strategy program may contribute to reducing the incidence and severity of ADRs especially in this group.
Keywords: cancer